Analisis Penerapan Akuntansi Syariah terhadap Transaksi Murabahah pada Bank Pembiayaan Rakyat Syariah (BPRS) - Samad, Musyakirah; Selvi Dewi Astina Sultan; Masyhuri (Journal of Islamic Economic Studies, 2025)
This research aims to analyze the implementation of Islamic accounting for murabahah transactions at Sharia Rural Banks (Bank Pembiayaan Rakyat Syariah (BPRS). Murabahah, as one of the main financing products in BPRSs, has specific characteristics that need to be recognized and measured in accordance with applicable Islamic accounting principles. This research employs a qualitative approach with a case study method at one BPRS. Data were collected through in-depth interviews with management and related staff, as well as the review of financial report documents and company accounting policies. The results of the study indicate that the BPRS under investigation has implemented most of the Islamic accounting provisions in recording and reporting murabahah transactions, including revenue recognition, measurement of acquisition costs, and relevant disclosures.